Nitrogen Containing Heterocycles as Anticancer Agents: A Medicinal Chemistry Perspective - Kumar, Adarsh; Singh, Ankit Kumar; Singh, Harshwardhan; Vijayan, Veena; Kumar, Deepak; Naik, Jashwanth; Thareja, Suresh; Yadav, Jagat Pal; Pathak, Prateek; Grishina, Maria; Verma, Amita; Khalilullah, Habibullah; et al. (Pharmaceuticals (Basel, Switzerland), 2023)
Cancer is one of the major healthcare challenges across the globe. Several anticancer drugs are available on the market but they either lack specificity or have poor safety, severe side effects, and suffer from resistance. So, there is a dire need to develop safer and target-specific anticancer drugs. More than 85% of all physiologically active pharmaceuticals are heterocycles or contain at least one heteroatom. Nitrogen heterocycles constituting the most common heterocyclic framework. In this study, we have compiled the FDA approved heterocyclic drugs with nitrogen atoms and their pharmacological properties. Moreover, we have reported nitrogen containing heterocycles, including pyrimidine, quinolone, carbazole, pyridine, imidazole, benzimidazole, triazole, β-lactam, indole, pyrazole, quinazoline, quinoxaline, isatin, pyrrolo-benzodiazepines, and pyrido[2,3-d]pyrimidines, which are used in the treatment of different types of cancer, concurrently covering the biochemical mechanisms of action and cellular targets.